Socioeconomic Factors, Parenting Styles, Bullying, and Adolescent Mental Health in Surakarta, Central Java, Indonesia - Dwi Kurniawati; Sri Mulyani; Okid Parama Astirin; Setyo Sri Rahardjo; Ika Sumiyarsi Sukamto (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: According to the World Health Organization (WHO) in 2018, approximately 970 million people worldwide live with mental disorders, with anxiety and depression being the most prevalent. In Indonesia, mental health problems are particularly common among adolescents; the 2022 Indonesian Adolescent Mental Health Survey (I-NAMHS) reported that 34.9% experienced mental health issues in the past year. In Surakarta, 597 cases of mental health problems were recorded between January and June 2024, with adolescents aged over 15 years accounting for 5.51% of cases. This study examined the direct and indirect effects of socioeconomic status, parenting styles, and bullying on adolescent mental health in Surakarta. Subjects and Method: A quantitative cross-sectional study was conducted on 200 respondents selected through multistage random sampling in three secondary schools. The independent variables were socioeconomic status, parenting styles, and bullying. The dependent variable was mental health. Data were collected using questionnaires and analyzed using simple logistic regression and path analysis. Results: The risk of mental health problems decreased with higher socioeconomic status (b= −1.59; 95% CI= −2.63 to −0.55; p = 0.003), positive parenting practices (b= −0.87; 95% CI= −1.68 to −0.61; p= 0.035), and a lower frequency of bullying (b = 1.77; 95% CI = 1.02 to 2.51; p < 0.001). Conclusion: This study concludes that mental health disorders decrease if adolescents have high socioeconomic status and good parenting patterns applied by their parents. Mental health disorders increase if adolescents experience high frequency of bullying. And this path analysis model shows good fit